2013
DOI: 10.1152/ajpcell.00109.2013
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and postsynaptic modulations of hypoglossal motoneurons by α-adrenoceptor activation in wild-type and Mecp2−/Y mice

Abstract: Hypoglossal motoneurons (HNs) control tongue movement and play a role in maintenance of upper airway patency. Defects in these neurons may contribute to the development of sleep apnea and other cranial motor disorders including Rett syndrome (RTT). HNs are modulated by norepinephrine (NE) through α-adrenoceptors. Although postsynaptic mechanisms are known to play a role in this effect, how NE modulates the synaptic transmissions of HNs remains poorly understood. More importantly, the NE system is defective in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…Experimental evidence indicates that the Mecp2 disruption causes an increase in neuronal activity or excitability in the brainstem, hippocampus, and neocortex (Stettner et al, ; Zhang et al, , ; Katz et al, ; Taneja et al, ; Calfa et al, , ; Gantz et al, ; Kron et al, ; Jin et al, ,; Ramirez et al, ). This is associated with decreased GABA inhibition, increased glutamate concentration and defects in intrinsic membrane properties, although defects in NMDA, AMPA, NE, serotonin, dopamine, and acetylcholine neurotransmitter/neuromodulator systems have also been found, some of which have excitatory effects (Katz et al, ; Ramirez et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidence indicates that the Mecp2 disruption causes an increase in neuronal activity or excitability in the brainstem, hippocampus, and neocortex (Stettner et al, ; Zhang et al, , ; Katz et al, ; Taneja et al, ; Calfa et al, , ; Gantz et al, ; Kron et al, ; Jin et al, ,; Ramirez et al, ). This is associated with decreased GABA inhibition, increased glutamate concentration and defects in intrinsic membrane properties, although defects in NMDA, AMPA, NE, serotonin, dopamine, and acetylcholine neurotransmitter/neuromodulator systems have also been found, some of which have excitatory effects (Katz et al, ; Ramirez et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Several groups of respiratory neurons and motoneurons are modulated by NE because NE augments cellular excitability via ␣ adrenoceptors (62,63). This NEergic modulation relies on firing activity and NE biosynthesis in LC neurons.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we showed the postsynaptic modulation of hypoglossal motoneurons (HNs) by NE (Jin et al, ). These neurons may remain to be modulated in the medullary slice preparation because the NEergic neurons are found in area postrema (Viemari, et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…One group of brainstem neurons targeted by NE modulation is the HNs. NE augments their firing activity by pre‐ and postsynaptic mechanisms (Jin et al, ). Such an NEergic modulation is defective in Mecp2 null mice, suggesting that HNs are ideal for testing NE modulation in our TH‐ChR‐ Mecp2 −/Y mice.…”
Section: Discussionmentioning
confidence: 99%